IMPROVING THE PROCESS OF CHILD-ORIENTED EDUCATION IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Tleumbetova Kalligul Dlimbetovna; Sultanova Nazokat (Journals Park Publishing, 2023)
In the realm of early childhood education, fostering a child-oriented approach is imperative for laying the foundation of a child's lifelong learning journey. Preschool education is a critical phase in a child's development, shaping their cognitive, emotional, and social skills. A child-oriented approach places the child at the center of the learning experience, acknowledging their unique needs, interests, and abilities. This article delves into methods to enhance child-oriented education in preschools, aiming to provide a framework that fosters holistic development and sets the stage for a successful educational journey.
Keywords: Child-oriented education, Preschool, Early childhood development, Teacher training, Curriculum adaptation, Play-based learning, Socio-emotional skills, Parental involvement.